Analisis Pengelolaan Anggaran Pendapatan Dan Belanja Desa Di Desa Patumbak Marindal II Kecamatan Patumbak Kabupaten Deli Serdang - Riski Nata Susanti Panjaitan; Ardin Dolok Saribu; Herti Diana Hutapea (Jurnal Minfo Polgan, 2025)
This study aims to determine the process of planning, implementation, administration, reporting and accountability. The Village Revenue and Expenditure Budget is in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning village financial management. This study is a type of qualitative descriptive research using primary data and secondary data, where the primary data is in the form of direct observation results in the form of interviews regarding the planning, implementation, administration, reporting and accountability of the Village Budget of Patumbak Marindal II Village, Deli Serdang District in 2023 while the secondary data from this study were obtained from documents of the Patumbak Marindal II Village government, Deli Serdang District. This data was obtained from available documents. This study uses data analysis techniques by means of data consistency and data presentation and drawing conclusions. The results of this study indicate that the management of the Village Budget of Patumbak Marindal II Village, Deli Serdang District, including planning, implementation, administration, reporting and accountability has been carried out in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018.